Implementasi Manajemen Sumber Daya Tenaga Kependidikan Dalam Meningkatkan Kualitas Layanan Pendidikan Agama Islam Pada Siswa Di SMA Negeri 1 Indralaya - Siti Utami Ayu Niswati (UNISAN JURNAL, 2024)
This research aims to investigate the implementation of education personnel resource management in improving the quality of Islamic religious education services at SMA Negeri 1 Indralaya. The research method used is qualitative research with a case study approach. Data was collected through in-depth interviews with related educational staff, direct observation, and analysis of related documents. Research findings show that the implementation of education personnel resource management plays an important role in improving the quality of Islamic religious education services at SMA Negeri 1 Indralaya. Factors that influence this implementation include the competence of educational staff, motivation, management support, and a conducive work environment. This research also identified several challenges faced in implementing educational resource management, such as limited resources, resistance to change, and lack of coordination between staff. Based on these findings, recommendations are presented to improve implementation effectiveness, including staff training and development, providing appropriate incentives, strengthening communication and collaboration between staff, and better resource allocation. This research contributes to the understanding of the importance of management of educational personnel resources in the context of Islamic religious education in high schools and provides guidance for related parties in improving the quality of Islamic religious education services for students.